The significance of extrinsic motivation as a strategy to improve employee productivity: a case of Athienitis Fife Avenue Supermarket - Cheteni, Nyaradzo (Midlands State University, 2017)
The research sought to determine the importance of extrinsic motivation in the management of people at work in achieving organizational objectives. The research was carried out at the Athienitis Fife Avenue Supermarket (AFVS). Research objectives were to ascertain if extrinsic motivation influences employee productivity, determine effectiveness of rewards offered and to identify the barriers in keeping up with employee motivation and productivity. The basic theories of motivation and the model of extrinsic and intrinsic motivation formed the basis of the theoretical framework. The study was descriptive and comparative analysis of data gathered as well as literature review was done. A sample of 25 participants including managerial and non managerial employees took part in the study. The research utilized questionnaires and interviews to gather data from research participants. During the analysis of the findings it was evidenced that employees at AFV are not de-motivated or motivated rather there is need for a balanced reward system which is to be renewed. Therefore low productivity has been influenced not only by employees’ level of motivation but also by other organizational issues. From the research it was concluded that motivational rewards are a necessity that organisations can use to motivate employees’ but only in the right quantities and quality hence improving employee performance. The researcher recommended the organisation to invest more in the reward processes as well as address the issue of organizational culture and policy to employees to facilitate a positive employee productivity and organizational reputation.